Analysis of the implementation of the Merdeka Curriculum policy in senior high schools: A case study on the practice level of learning - Budiarti, Erna; Jannah, Ratu Roihatul; Chaedar, Al; Solehudin, Rd. Heri (Harmoni Sosial: Jurnal Pendidikan IPS, 2024)
The Merdeka Curriculum Policy is a strategic step in Indonesia's educational reform, and this study is a collaborative effort to understand its implementation at the Senior High School (SMA) level. We aim to conduct an in-depth analysis, with particular attention to the process of understanding, application, and its impact on teaching and learning activities. The research employs a qualitative approach using data collection techniques such as field observations, in-depth interviews, and document analysis. The primary respondents are teachers, students, and school staff actively involved in the policy implementation, making this a truly inclusive and comprehensive study. The findings reveal that implementing the Merdeka Curriculum Policy in high schools faces challenges, such as inconsistent understanding of the policy among teachers, the need for ongoing training to enhance teacher competencies, and infrastructure limitations that hinder optimal application. Nevertheless, notable successes include increased creativity in learning, active student engagement in learning processes, and the emergence of innovations in teaching methods. Further analysis indicates that active teacher participation and managerial support from the school are critical success factors in implementing this policy. This research is not just an academic exercise but a practical guide for the development of educational policies. By providing insights into the challenges and opportunities of implementing the Merdeka Curriculum, we aim to empower policymakers with the knowledge to design more effective implementation strategies. This study also serves as a beacon of hope for other schools facing similar situations, offering practical guidance and enriching the academic literature on the dynamics of educational policy in Indonesia, particularly at the high school level.